Communicative activity in teaching professionally oriented English: a methodological aspect - Sagiyeva, A.T.; Utegenova, A.N.; Rakisheva, Zh.B. (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
New conditions determine new requirements to the quality of specialists’ training for professional activity. It is necessary to emphasize the important role of communicative activity development in professional-personal direction. The purpose of this article ― to systematize the results obtained in the framework of pedagogical research conducted on the basis of Aktobe Regional University named after K. Zhubanov, with the 3rd year students of the specialty “5B010200 ― “Pedagogy and Methods of Primary Education”” with the Kazakh language of training. Scientific importance is designated by means of allocation of theoretical and conceptual device, practical importance consists in the chosen and tested complex of diagnostics, and techniques on communicative activity. The methodology of research is based on activity (A. N. Leontiev, V. A. Slastenin, etc.) and acmeological (N. V. Kuzmina, etc.) approaches, review-analytical and diagnostic research methods. The main results of the study were the systematization of the identified components of communicative activity, methods and techniques for teaching foreign language to students of non-linguistic specialties. The value is the cultural enrichment of the student on the basis of competently selected teaching material. The practical value of the results of the work is based on methodological recommendations to university faculty working in this area.
Кәсіби бағдарлы ағылшын тілін оқытудағы коммуникативтік белсенділік: әдістемелік аспект
Коммуникативная активность в обучении профессионально-ориентированному английскому языку: методологический аспект
Keywords: learning; communicative readiness; student; component; foreign language; quality; specialty; technique